2017
DOI: 10.1021/acsami.7b09270
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Polymer–Inorganic Hybrid Materials through Synergistic Mutual Doping of the Constituents

Abstract: Polymer-matrix-based inorganic-organic hybrid materials are at the cutting edge of current research for their great promise of merging properties of soft and hard solids in one material. Infiltration of polymers with vapors of reactive metal organics is a pathway for postsynthetic blending of the polymer with inorganic materials. Here, we show that this process is also an excellent method for fabricating conductive hybrid materials. Polyaniline (PANI) was infiltrated with ZnO and the initially insulating polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…In the specific case of ZnO films grown by atomic layer deposition (ALD) which are of particular interest, because of their industrial potential as they combine good structural quality of the deposited films, cost effectiveness, and possibility to cover large substrates, [ 16–19 ] previous studies have reported on hydrogen/intrinsic defects interaction with the dopants introduced and on the dependence of the hydrogen concentration on the deposition temperature and its anticorrelation with the measured carrier concentration. [ 20,21 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the specific case of ZnO films grown by atomic layer deposition (ALD) which are of particular interest, because of their industrial potential as they combine good structural quality of the deposited films, cost effectiveness, and possibility to cover large substrates, [ 16–19 ] previous studies have reported on hydrogen/intrinsic defects interaction with the dopants introduced and on the dependence of the hydrogen concentration on the deposition temperature and its anticorrelation with the measured carrier concentration. [ 20,21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, according to the present knowledge, the role of hydrogen is more intricate with a range of hydrogen-native point defect complexes influencing the resulting ZnO conductivity. [6,[11][12][13][14][15] In the specific case of ZnO films grown by atomic layer deposition (ALD) which are of particular interest, because of their industrial potential as they combine good structural quality of the deposited films, cost effectiveness, and possibility to cover large substrates, [16][17][18][19] previous studies have reported on hydrogen/ intrinsic defects interaction with the dopants introduced and on the dependence of the hydrogen concentration on the deposition temperature and its anticorrelation with the measured carrier concentration. [20,21] Overall, in as-grown ZnO-ALD films, hydrogen concentrations are typically at the level of %10 20 -10 21 at cm À3 , which is emphatically above the actual electron concentrations derived from Hall effect measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide films can be obtained by many growth techniques such as pulsed laser deposition (PLD), radio‐frequency magnetron sputtering, chemical vapor deposition (CVD), or molecular beam epitaxy (MBE) . Atomic layer deposition (ALD) has several advantages over other growth methods, among which are a precise control of thickness at the nanometer scale, a possibility to perform deposition on large substrates, or an opportunity to obtain thin ZnO films at temperatures low enough for deposition on organic substrates or in the back end Of line (BEOL) technology . Polycrystalline ZnO films grown at low temperature (LT) are of considerable importance for hybrid organic/inorganic electronics and 3D memory devices that posted severe restrictions on deposition temperature, which is required not to exceed 150 °C .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the redox behavior of PANI provided self-healing properties to the intentionally scratched coatings 40 . Furthermore, synthesis of epoxy-doped Clay-PANI nanocomposites with different metal oxide nanoparticles such as ZnO 41 , 42 , TiO 2 43 , SiO 2 44 , Fe 2 O 3 45 , 46 , ZrO 2 47 and Al 2 O 3 48 was found to improve the corrosion protection of carbon steel via the adjustment of the interaction between the clay-PANI nanocomposites and the added metal oxide Nano-species 49 51 . The most discussed mechanism of PANI based nanocomposites in the literature is the called “ennobling mechanism” 52 .…”
Section: Introductionmentioning
confidence: 99%